Metformin Radiosensitizes p53-Deficient Colorectal Cancer Cells through Induction of G2/M Arrest and Inhibition of DNA Repair Proteins - Jeong, Youn Kyoung (PLoS One, 2015)
The present study addressed whether the combination of metformin and ionizing radiation (IR) would show enhanced antitumor effects in radioresistant p53-deficient colorectal cancer cells, focusing on repair pathways for IR-induced DNA damage. Metformin caused a higher reduction in clonogenic survival as well as greater radiosensitization and inhibition of tumor growth of p53(-/-) than of p53(+/+) colorectal cancer cells and xenografts. Metformin combined with IR induced accumulation of tumor cells in the G2/M phase and delayed the repair of IR-induced DNA damage. In addition, this combination significantly decreased levels of p53-related homologous recombination (HR) repair compared with IR alone, especially in p53(-/-) colorectal cancer cells and tumors. In conclusion, metformin enhanced radiosensitivity by inducing G2/M arrest and reducing the expression of DNA repair proteins even in radioresistant HCT116 p53(-/-) colorectal cancer cells and tumors. Our study provides a scientific rationale for the clinical use of metformin as a radiosensitizer in patients with p53-deficient colorectal tumors, which are often resistant to radiotherapy.